Analysis of Factors Influencing BPJS Membership Status in the Independent (PBPU) and Non-Worker Segments - Andi Eka Putra; Pujiyanto (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Universal Health Coverage (UHC) is a significant agenda outlined in the SDG 2030. In order to achieve UHC, Indonesia established the Social Security Management Agency (BPJS) in 2014. Nearly a decade after its establishment, BPJS experienced a financial deficit in its first six years, followed by a surplus during the COVID-19 pandemic. This has impacted the sustainability of BPJS Health. One of the factors contributing to the financial deficit is the non-compliance of participants in paying BPJS contributions, particularly in the Non-Wage Earner/Self-Employed/Independent (PBPU) and Non-Worker segments who are required to pay contributions individually. When participants fail to pay contributions for six consecutive months, their membership status is converted to inactive. From the 2022 BPJS Sample Data, it was found that 799,384 out of 2,305,435 (34.67%) participants had inactive membership status. Objective: This study aims to analyze the factors influencing BPJS membership status in the Independent and Non-Worker segments. Method: The method that used in this study is quantitative analysis of secondary data from the 2022 BPJS Sampel Data with the Linear Probability Model (LPM), Logit and Probit Models. The analysis is conducted using STATA to obtain univariate, bivariate and multivariate analyses. Result: From a sample of 545,507 participants, if was found that 54.20% had inactive membership status. Factors such as age, gender, marital status, treatment class, healthcare facility type, and participant segmentation affect membership status. The LPM regression results indicate that the factors leading to inactive membership status are being of productive age, male, belonging to class 1 and 2, utilizing primary healthcare facilities, and being in the Independent segment. Conclusion: Therefore, stateholders such as the central government and BPJS need to collaborate in efforts to reduce the number of inactive membership statuses.